The genus Lernaeenicus Lesueur (Copepoda, Siphonostomatoida, Pennellidae) in India: a checklist with notes on its taxonomy and ecology - Raja, Kuzhanthaivel; Saravanakumar, Ayyapan; Gopalakrishnan, Ayyaru; Vijayakumar, Ramalingam; Hwang, Ui Wook; Maran, Balu Alagar Venmathi (Zootaxa, 2016)
Members of the pennellid genus Lernaeenicus Lesueur, 1824 (Copepoda, Siphonostomatoida) have frequently been recorded from commercially important fishes collected along the coasts of India. Marine fish hosts from landing centres at Nagapattinam and Parangipettai Tamil Nadu, southeast coast of India, were examined for parasitic copepods between January 2011 and December 2013. A total of nine species including three unidentified species of Lernaeenicus were recorded: (1) L. alatus Rangnekar, 1962 from the Indo-Pacific king mackerel Scomberomorus guttatus (Bloch & Schneider, 1801), (2) L. anchoviellae Sebastian & George, 1964 from the golden trevally Gnathanodon speciosus (Forsskål, 1775), (3) L. hemirhamphi Kirtisinghe, 1932 from the blue-barred halfbeak Hemiramphus far (Forsskål, 1775), Lutke’s halfbeak H. lutkei Valenciennes in Cuvier & Valenciennes, 1847a and the ribbon halfbeak Euleptorhamphus viridis (van Hasselt, 1823b), (4) L. polynemi Bassett-Smith, 1898 from the fourfinger threadfin Eleutheronema tetradactylum (Shaw, 1804), (5) L. seeri Kirtisinghe, 1934 from the wahoo Acanthocybium solandri (Cuvier in Cuvier & Valenciennes, 1832), (6) L. stromatei Gnanamuthu, 1953 from the black pomfret Parastromateus niger (Bloch, 1795), (7) Lernaeenicus sp. 1 from the Indian anchovy Stolephorus indicus (van Hasselt, 1823a) and the rainbow sardine Dussumieria acuta Valenciennes in Cuvier & Valenciennes, 1847b, (8) Lernaeenicus sp. 2 from the goldspot mullet Chelon parsia (Hamilton, 1822), and (9) Lernaeenicus sp. 3 from the flathead grey mullet Mugil cephalus Linnaeus, 1758. Four pennellid species (L. hemirhamphi, L. polynemi, L. seeri and L. stromatei) were studied for their seasonal occurrence including prevalence and mean intensity, both of which were high in postmonsoon (2011) and low in premonsoon (2013) seasons. A checklist is provided for the Indian species of Lernaeenicus.